Geochemistry of Proterozoic carbonates, Belt Supergroup, Montana and Idaho, U.S.A. - Hall, Susan Margaret. (University of Ottawa (Canada), 1990)
An increase in the degree of post-depositional alteration of Belt limestones is reflected in a diminution of Sr and Mg content, increase in Mn and by depletion in $\sp $C and $\sp $O. $\delta\sb1\sp8$O of limestones ranges from +13.4 to +22.9$\perthous$ SMOW and $\delta\sp $C from $-$5.6 to +2.4$\perthous$ PDB. Two diagenetic trends can be resolved for the limestones. One, affecting the presumed originally aragonite-rich sediments, comprises the Newland, Libby and perhaps the Snowslip Formations. The other trend is confined to the Middle Belt Carbonate and may have been controlled by high-Mg calcitic sediments. A regional westward depletion in $\sp $O of 8$\perthous$ and $\sp $C of 2.5$\perthous$ reflects a higher temperature of alteration (300$\sp\circ$C) and an increased contribution from CO$\sb2$ derived from thermal cracking of hydrocarbons in the western Belt basin. The $\delta\sp $O and $\delta\sp $C compositions of the Belt limestones are within the ranges of the values reported for coeval Proterozoic basins. If compared to the modern ocean, the $\delta\sp $O of the Belt sea may have been lighter by perhaps 7$\perthous$. $\delta\sp $C averages close to 2$\perthous$, similar to modern values. Dolostones in the Belt basin are dominantly micritic, with good preservation of depositional textures. $\delta\sp $O of dolomite ranges from 18.1 to 27.9$\perthous$ SMOW and $\delta\sp $C from $-$2.2 to 1.9$\perthous$ PDB. Post-depositional alteration of dolostone is indexed by a decrease in Sr and Na contents, increase in Mn and by depletion in $\sp $O and $\sp $C. Dolostones of the Mt. Shields and Altyn Formations have low Sr and heavy $\delta\sp $O and $\delta\sp $C (if compared to the bulk of Belt samples), show pervasive and destructive dolomitization and may have formed in a mixed water zone of the Dorag type. The remainder of the Belt dolostones resemble typical 'early' diagenetic micritic dolostones in their high Sr content and may have formed in an evaporative setting. Carbonates of mixed dolomite and calcite composition show depletion in $\sp $O and $\sp $C and increase in Mn content with progressive diagenetic alteration. Secular variations in $\delta\sp $C are superimposed on diagenetic trends in this population, showing that carbonates of the Spokane/Greyson, Libby and Newland Formations are $\approx$2$\perthous$ heavier than those of the Middle Belt Carbonate. $\sp‡$Sr/$\sp†$Sr of Belt carbonates range between 0.70484 and 0.74991. Progressive diagenesis, as indexed by decreasing elemental Sr and depletion in $\sp $O and $\sp $C, results in an increase in $\sp‡$Sr/$\sp†$Sr values. $\sp‡$Sr/$\sp†$Sr is better preserved in dolomitized rocks and rocks with initially high Sr content (the Newland and Greyson/Spokane Formations). The 'best', that is the least radiogenic values, are similar to those for previously published coeval Proterozoic carbonates and they are more radiogenic than the contemporaneous mantle. A comparison of $\sp‡$Sr/$\sp†$Sr for the dissolved vs. the suspended load of the Belt basin indicates that the rivers supplying strontium to the basin did not exclusively drain young volcanic or plutonic terrain, but this terrain must have contained a significant source of Sr with marine isotopic composition. Alternatively, the source of nonradiogenic Sr might have been marine waters. (Abstract shortened by UMI.)
Keywords: Geochemistry.